Preserved cardiovascular homeostasis despite blunted acetylcholine‐induced dilation in mice with endothelial muscarinic M3 receptor deletion. (18th February 2019) - Rhoden, Alexandra; Speiser, Jakob; Geertz, Birgit; Uebeler, June; Schmidt, Kjestine; de Wit, Cor; Eschenhagen, Thomas
Abstract: Aim: Muscarinic acetylcholine receptors (AChMR1‐5) are fundamental for cellular responses upon release of the neurotransmitter acetylcholine (ACh) from parasympathetic nerve fibers. ACh is the prototypical agonist stimulating endothelium‐dependent dilation, but most blood vessels lack parasympathetic innervation, raising the question as to the physiologic function of endothelial AChMR in vivo. Global deletion of AChM3R revealed a role in ACh‐induced vasodilation in vitro and food uptake, but overall cardiovascular homeostasis has not been examined thoroughly. Methods: To characterize the function of endothelial AChM3R in vivo, we deleted AChM3R specifically in endothelial cells with an inducible or a non‐inducible Cre‐loxP system, driven by the endothelium‐specific promoters VE‐cadherin (indEC‐M3R −/− ) or TIE2 ( tek2 ; EC‐M3R −/− ) and examined arteriolar dilation in the cremaster microcirculation, arterial pressure and cardiac function in these mice in vivo. Results: In both EC‐M3R −/−, ACh‐induced dilation was strongly impaired in arterioles in vivo, while responses to other dilators were mostly preserved. However, arterial pressure (indEC‐M3R −/− ) and arteriolar tone as a surrogate for peripheral vascular resistance did not differ between EC‐M3R −/− and control mice. Aged EC‐M3R −/− mice (74‐78 weeks) did not differ in body weight, heart weight, cardiac structure or contractile function from controls. Conclusion: We conclude that AChM3R elicits the endothelium‐dependent dilation upon ACh also in arterioles in vivo. Despite this prominent role, the endothelial deletion of AChM3R does not affect overall cardiovascular homeostasis. Thus, their physiologic function in endothelial cells remains obscure.